CONVERSION OF LAPAROSCOPIC CHOLECYSTECTOMY TO OPEN CHOLECYSTECTOMY: PREOPERATIVE RISK FACTORS AND INTRAOPERATIVE REASONS - Umairah Yaqub (Army Medical College Rawalpindi, 2020)
Objective: To identify the frequency, associated risk factors and intraoperative reasons for conversion of Laparoscopic Cholecystectomy to open Cholecystectomy.